A Meta-analysis of the Impact of COVID-19 on Stroke Mortality - HUANGFU Xiaojuan, LI Xiaojuan, CHEN Min, LIU Jihong, ZHAI Rui, CAI Zhipeng, LI Litao (Zhongguo quanke yixue, 2023)
Background The COVID-19 pandemic seriously affects human health and life. COVID-19 has been reportedly associated with a high risk of thrombotic events, which are closely associated with stroke. Objective To assess the effect and possible mechanism of COVID-19 on stroke morbidity, providing a reliable theoretical basis for scientific prevention and treatment of COVID-19 in stroke. Methods We searched databases of Web of Science, PubMed, EmBase, Cochrane Library, CNKI and Wanfang Data for cohort studies and case-control studies related to COVID-19 and stroke published from December 2019 to January 2022. Two researchers conducted literature screening and data extraction separately. The Newcastle-Ottawa Scale was used to assess the quality of included studies. Meta-analysis was used to evaluate the impact of COVID-19 on stroke mortality. Funnel plot was used to evaluate the potential publication bias. Results A total of 18 studies were included, 12 of them were of good quality, and other 6 were of fair quality. Meta-analysis showed that stroke patients with COVID-19 had higher mortality〔RR=4.16, 95%CI (2.82, 6.13) , P<0.000 01〕, prolonged prothrombin time (PT) 〔MD=0.78, 95%CI (0.35, 1.20) , P=0.000 3〕, higher D-dimer level〔MD=1.34, 95%CI (0.83, 1.84) , P<0.000 01〕 and higher NIHSS score〔MD=6.66, 95%CI (4.54, 8.79) , P<0.000 01〕, as well as younger age〔MD=-2.04, 95%CI (-3.48, -0.61) , P=0.005〕than those without COVID-19. There was no statistically significant difference in activated partial thromboplastin time between stroke patients with and without COVID-19〔MD=2.51, 95%CI (-2.69, 7.71) , P=0.34〕. Funnel plot assessing potential publication bias in the impact of COVID-19 on stroke mortality was basically symmetrical. Conclusion COVID-19 could increase the risk of stroke mortality, which may be related to alterations in the coagulation system manifested by abnormal PT and D-dimer level and so on. And the outcomes of stroke patients with COVID-19 were associated with age and NIHSS score at admission.